2010
DOI: 10.1111/j.1600-0668.2010.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde measurements in residential indoor air using a developed sensor element in the Kanto area of Japan

Abstract: This study contributed to the measurements of indoor formaldehyde levels. We have used a newly developed sensor for time-integrated measurements of formaldehyde concentrations. This sensor does not need a power supply during exposure to air, and does not need special skills to use. This research showed that homeowners successfully deployed the sensor at the desired place and desired period in their house by themselves. Formaldehyde is emitted by various off-gassing sources, such as furniture. Therefore, for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
2
11
0
Order By: Relevance
“…The results show that emissions increased by 9% from 10 (0.036) with a 1 °C increase in temperature. This agreed well with the 10% increase reported previously [14] Therefore, equation (5) can express the relationship of C (μg/g) to AbsB within the temperature range 10 °C to 40 °C:…”
Section: Temperature Dependencesupporting
confidence: 91%
See 2 more Smart Citations
“…The results show that emissions increased by 9% from 10 (0.036) with a 1 °C increase in temperature. This agreed well with the 10% increase reported previously [14] Therefore, equation (5) can express the relationship of C (μg/g) to AbsB within the temperature range 10 °C to 40 °C:…”
Section: Temperature Dependencesupporting
confidence: 91%
“…The plastic bag was placed on an indoor desk in darkness for 1 h. The element was then quickly removed and placed into an aluminum-coated polyethylene bag for 30 min, and absorbance was measured at 414 nm (Abs solB1 ). The reason for keeping the sensor in darkness (in the aluminum-coated bag) for an additional 30 min is to ensure full completion of the reaction in the sensor element [14]. The change in absorbance registered by the sensor element is proportional to formaldehyde concentration in the polyethylene bag.…”
Section: Determining Formaldehyde Emitted From Textiles Using a Sensomentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, participants experiencing recent indoor renovation showed the odds ratios of 1.9 (95% CI: 1.4-2.7) for eczema 17. As the level of formaldehyde increases in cases of moving to a newly-built building or a renovated house,33,34 lowering formaldehyde level should be taken into account if there is a family member with AD.…”
Section: Discussionmentioning
confidence: 99%
“…in Japan; marketed by Shinyei and RKI based on Maruo et. al., 2008Maruo et. al., , 2010# Environmental Sensors Model Z300 measures HCHO by difference: An electrochemical sensor is periodically preceded by a formaldehyde scrubber (adapted from a NIOSH method.)…”
Section: Executive Summarymentioning
confidence: 99%